Application Framework Development for Halal Tourism Guide in Indonesia - Adhi Alfian; Marwah Aulia; Farhanny Destine; Sufia Nur Kamila (Universitas Padjadjaran, 2020)
Indonesia has the potential of abundant natural resources, supported by the advancement of Islamic culture. These provide opportunities for the development of halal tourism in Indonesia utilize technological developments by helping travellers in planning trip from a smartphone. This research aims to develop a framework for the halal tourism industry with the use of an Islamic trip guide application that simplifies and provides interesting direction on tourists' trip. It observes two main aspects which are the application framework of Islamic trip guide and the concept of halal tourism in Indonesia. Researchers collected preliminary data from questionnaires and interviews. Afterwards, develop an Islamic trip application framework that provides halal tourism points in various regions in Indonesia, at each destination, there is a mission or challenge trip that must be visited by the user. The results from the development of this application are the form of ease of access to halal tourism as well as increased interest from tourists to halal trips in Indonesia.